Does market structure matter for Islamic rural banks' profitability? - Agus Widarjono; M. B. Hendrie Anto (University of Merdeka Malang, 2020)
This study investigates the impact of the market structure including bank-specific factor and macroeconomic conditions on profitability of Islamic rural banks in Yogyakarta and Central Java provinces. We employ the Structure Conduct Performance (SCP) and Relative Market Power (MRP) hypothesis using static and dynamic panel data regression over the periods 2013Q1- 2018Q4. Diagnostic tests obviously confirm that the dynamic panel regression is more appropriate in estimating profitability because of the dynamic behavior of profitability, instead of the static panel regression. Based on the Concentration Ratio (CR) and the Herfindahl-Hirschman Index (HHI), both provinces face imperfect competition market. Market share positively affect profitability but market concentration has no impact on profitability. The results clearly show that our study supports the RMP hypothesis but fail to confirm the SCP hypothesis. Some control variables such as the level of efficiency and financing rate also affect profitability. A high level of operating efficiency increases more profits and low non-performing financing produce more profits. Our findings suggest that improving operating cost eventually is the key in capitalizing the power of market share. JEL Classification: G21, G24DOI: https://doi.org/10.26905/jkdp.v24i4.4810